PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Butarbutar, Hilary Hana Rumondang; Rajagukguk, Waminton (Universitas Insan Budi Utomo, 2026)
This study aimed to analyze the influence of using the Game Based Learning (GBL) model assisted by Wordwall on students’ mathematical critical thinking ability, as well as to determine the extent of its impact in mathematics learning. The research employed a quasi-experimental design with a Non-Equivalent Control Group Pretest-Posttest Design, conducted in the odd semester of the 2025/2026 Academic Year at SMP Negeri 37 Medan. The sample consisted of two classes: the experimental class, which learned using the Game Based Learning model assisted by Wordwall, and the control class, which learned through conventional methods. The research instrument was a descriptive test consisting of three essay questions assessing four indicators of critical thinking ability: interpretation, analysis, evaluation, and inference. (1) The results of the analysis showed that the mean pretest score of the experimental class was 43.62, increasing to 76.24 on the posttest, while the control class increased from 48.89 to 63.02. The Mann-Whitney test yielded a significance value of , indicating a significant influence of the GBL model assisted by Wordwall on students’ critical thinking ability. (2) The N-Gain score of the experimental class was 0.5790 (medium category) and the Effect Size was 0.81 (large category), indicating that the GBL model has a strong and effective influence on improving students’ mathematical critical thinking ability.